The Efforts of the Sabhara Unit Patrol Unit in Preventing Crime of Motor Vehicle Theft in Sumedang Police Jurisdiction: Upaya Unit Patroli Satuan Sabhara dalam Mencegah Tindak Pidana Pencurian Kendaraan Bermotor di Wilayah Hukum Polres Sumedang - Prakoso, Bagus Maharta (Akademi Kepolisian Republik Indonesia, 2021)
This research is motivated by the high number of motor vehicle theft cases compared to other crimes in Sumedang. The Indonesian Police need to conduct patrols to prevent the meeting of intentions and opportunities for perpetrators of crimes, especially in the theft of motorized vehicles. Therefore the purpose of this study is to describe the general description of motor vehicle theft and patrol unit efforts and the factors that influence the efforts of Sabhara patrol units in preventing motor vehicle theft. The research approach used is qualitative with the type of field research. Data sources include primary and secondary data collected by interview, observation, and document review techniques. The validity of the data is tested through the triangulation technique of sources, techniques, and time, while the data analysis is carried out with the stages of data reduction, data presentation, and drawing conclusions. Theories, discourses, and ideas used to dissect the problem include the theory of routine activities, the theory of law effectiveness, and Perkabaharkam Polri No. 1 of 2017 about Patrol. The results of the study concluded that the crime of motor vehicle theft was ranked highest in the jurisdiction of the Sumedang District Police. This happens because the fulfillment of the three elements in Routine Activity Theory. The Sabhara Police Unit Sumedang Patrol Activity is carried out based on Perkabaharkam Polri No. 1 of 2017, divided into 4 (four) stages, namely the preparatory stage, the implementation phase, the termination stage, and the supervision, control and ‘analysis and evaluation’ stage. In conducting patrols, the Sumedang Police patrol unit has not yet fully complied with the provisions stipulated in Perkabaharkam No. 1 of 2017. Factors that influence the efforts of the Sabhara unit patrol unit consist of internal and external factors. Based on these findings, dialogical patrols should be carried out more often to raise awareness and create collaboration with the community, both individually and in groups, so that disturbances in security and public order especially motor vehicle theft can be prevented as early as possible. And sufficient members in accordance with their needs and provide appropriate training. In addition, the fulfillment and renewal of infrastructure facilities must be carried out to support the implementation of the tasks in order to achieve maximum results.